Breeding report of a new mid-ripening red pear cultivar Canyu - LI Longfei; GAO Lijuan; XU Jintao; JI Minghui; LIU Huan; ZENG Qingming; HAO Baofeng (Guoshu xuebao)
Canyu is a new mid-ripening pear cultivar (Pyrus communis) with red skin selected from the seedlings of Red Clapp's Favorite by Changli Institute of Pomology, Hebei Academy of Agriculture and Forestry Sciences. It was initially selected in 2008 and named 6-29. Through regional adaptability testing at three sites including Changli county, Caofeidian district and Botou city in Hebei province from 2015 to 2023, the main economic characters of 6-29 showed stable. The variety patent of Canyu was obtained in July 2020, and it was approved by the Hebei Provincial Forest Variety Approval Committee in 2024. In Changli area of Hebei province, the flowers bloomed in mid-April, and the flowering period lasted 7-10 days. The fruit development period was around 120 days and could be harvested in mid-August. The tree was vigorous and posture was open. The annual branches were reddish-yellow on the exposed side and straight in shape with short internodes. The leaf buds were adnate. The color of the tender leaves was green. The mature leaves were elliptic in shape with serrate, long gradually acuate and round base. The number of flowers in each inflorescence was from five to seven. The flowers were pink, ovate, and the relative position of the petals was overlap, the position of stamen was lower than that of the stigma. The color of the anther was fuchsia. The fruit shape was wide-necked, has green yellow ground color and nacarat over color. The average fruit mass was 325.1 g. The fruit peel was smooth with few russeting, the fruit dots were dense and medium in size. The color of fthe lesh was creamy white, melting and rich juicy, tasteed sour-sweet. The texture was fine with aroma. The fruit had no seeds. The soluble solids content was 14.5% with little stone cell and residue. The hardness of the flesh was 1.62 kg·cm-2. The quality was excellent. Canyu had a high bud burst capability and branch development capability. The fruit mainly beared fruits on the short branches, the fruit setting rate was high. The continuous fruiting capacity of the branches was strong. After 3 years of planting, it begined bearing. The yield was 3256 kg per 666.7 m2 in the seventh year at a density of 2.0 m×4.5 m. The variety had strong disease resistance and extensive ecological adaptability. The density of planting would be (1-3) m × (3.5-4.0) m. Xuehua, Yali, Huangguan pears were the most suitable pollination trees for it, and the configuration of the pollinizer was (4-5) ∶1. The suitable tree shape for Canyu was spindle. Attention should be paid to the management of fertilizer, water and pests in cultivation. It would be suitable for cultivation in Changli county, Caofeidian district and Botou city and other pear producing areas with similar ecological conditions in China.